Parametric Design and Motion Simulation Analysis of Non-circular Gear Planetary Gear Train - Yongping Liu; Xingwen Fu; Yongqiao Wei; Dawei Li (Jixie chuandong)
Non-circular gear planetary gear train is the core component of non-circular gear hydraulic motor， and its pitch curve design is the key to the overall structure design. Aiming at the problems of non-circular gear planetary gear train pitch curve of order 4-6， which is not unique and difficult to design， based on the design method of pitch curve of 4-6 order non-circular gear planetary gear train， the eccentricity is selected as the control parameter to design different pitch curves of non-circular gear planetary gear train. The influence of eccentricity on the motion characteristics of non-circular gear planetary gear train is compared and analyzed. The results show that， in the process of non-circular gear planetary gear train transmission， the center acceleration and angular acceleration of planetary gear will have a sudden change， and the mutation positions are at the maximum position of inner gear ring radial diameter， and with the increase of eccentricity of pitch curve， the abrupt values of center acceleration and angular acceleration of planetary gear increase.